1994
DOI: 10.1111/j.1751-1097.1994.tb05000.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Alterations of Actin in Cultured Human Keratinocytes and Fibroblasts Exposed to Long‐wavelength Radiations. Possible Involvement in the Uva‐induced Perturbations of Endocytotic Processes

Abstract: Exposure of cultured MRC5 human fibroblasts or NCTC 2544 human keratinocytes to mild doses of ultraviolet A (UVA: 320-400 nm) radiations markedly decreased the actin reactivity with fluorescein-labeled phalloidin. This indicates a change in the degree of polymerization of actin and thus in the organization of actin filaments. Such a phenomenon might be involved in the previously reported UVA-induced inhibition of specific and nonspecific endocytotic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
(1 reference statement)
1
13
0
Order By: Relevance
“…This result suggests that UVA might affect melanoma tumor angiogenesis, via enhanced VEGF expression, and this hypothesis will be studied further in a separate project. Finally, UVA radiation exposure has caused decrease the G-actin and cofilin gene expression levels agreeing with earlier studies that have shown that UVA radiation decreases actin expression in human fibroblasts and keratinocytes [21], and in mouse and hamster fibroblasts [22]. …”
Section: Discussionsupporting
confidence: 90%
“…This result suggests that UVA might affect melanoma tumor angiogenesis, via enhanced VEGF expression, and this hypothesis will be studied further in a separate project. Finally, UVA radiation exposure has caused decrease the G-actin and cofilin gene expression levels agreeing with earlier studies that have shown that UVA radiation decreases actin expression in human fibroblasts and keratinocytes [21], and in mouse and hamster fibroblasts [22]. …”
Section: Discussionsupporting
confidence: 90%
“…Alterations in cell adhesion have been described in cultured cells exposed to light (Bolognani et al, 1994;Djavaheri-Mergny et al, 1994). Photosensitization also induced changes in cell anchorage to certain extracellular components, which are associated to a low expression of b1-integrin in ovarian cancer cells (Runnels et al, 1999) and in fibroblasts (Margaron et al, 1996) after Verteporfin phototreatment.…”
Section: Discussionmentioning
confidence: 96%
“…This structural rearrangement may be responsible for the detachment of cells from adjacent surface, the cell body retraction and, as a consequence, the loss of contact between neighbouring cells. Previously, it was reported that UVA irradiation can lead to a markedly decreased actin reactivity with fluorescein‐labelled phalloidin (41). This effect was suggested to be a consequence of alternating actin polymerization and thus in the organization of actin filaments.…”
Section: Discussionmentioning
confidence: 99%